25-YEAR EXPERIENCE OF USING INTRAGASTRIC THERAPY TO TREAT DUODENAL ULCERS - Pisanniy, O.E.; Shevchenko, V.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
On the basis of experimental-clinical research a method of local dosed endoscopic cryotherapy to treat the chronic noncomplicated duodenal ulcers has been worked out. The method uses a specially developed instrument – cryoelectrocoagulator – that enables to perform cryotherapy of the pathologic focus through the biopsy probe of a fibrogastroduodenoscope. Therapeutic effect of endoscopic cooling of duodenal ulcers is caused by the stimulation of reparative processes in the pathologic focus, normalization of the stomach motor function, improvement of the alkalization function of mucus tunic in its part. The experience of using intragastric cryotherapy to treat duodenal ulcers (5873 patients) since 1979 till present time allows the authors to include this method in the arsenal of a complex treatment of chronic duodenal ulcers to shorten the time of the ulcer substratum repair, decrease the number of relapses and shorten the rehabilitation period.